2021
DOI: 10.1556/063.2021.00056
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gender stereotyping and demographic factors on academic choice: The case of the University of Debrecen

Abstract: Education is the proven guarantor of gender equality and sustainable development. Empirical evidence from previous studies in European countries (Favara, 2012; Geerdink & Dekkers, 2011; OECD, 2009) shows that women are incompletely represented in many areas of technical and scientific education. This study examined the impact of gender stereotypes and factors related to family background, university criteria, and the main factors influencing students’ academic choices at the University of Debrecen. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…It was well depicted that women opting for science, technology, engineering and mathematics (STEM) course degrees are being higher than their male counterparts but segregation exists even within STEM majors (Alon and DiPrete, 2015). Further studies on the impact of gender stereotypes and factors related to demographic variables on students' academic choices at the university was reported and found that there was no significant difference in the gender on the choices in the academics (Taher, 2022). The findings obtained in the present study indicate that the gender does not have any influence on the satisfaction levels and the choice of academic institution which are consistent with those of published reports.…”
Section: Discussionmentioning
confidence: 99%
“…It was well depicted that women opting for science, technology, engineering and mathematics (STEM) course degrees are being higher than their male counterparts but segregation exists even within STEM majors (Alon and DiPrete, 2015). Further studies on the impact of gender stereotypes and factors related to demographic variables on students' academic choices at the university was reported and found that there was no significant difference in the gender on the choices in the academics (Taher, 2022). The findings obtained in the present study indicate that the gender does not have any influence on the satisfaction levels and the choice of academic institution which are consistent with those of published reports.…”
Section: Discussionmentioning
confidence: 99%